The creation of a federal partnership : the role of the states in affordable housing - Brassil, Margaret M., 1959- (SUNY series on urban public policy., 2010)
With the ongoing recession and housing crisis, it has never been more important to understand the federal and state governments' roles in affordable housing. The Creation of a Federal Partnership takes a fresh look at the history of national and state housing policy by examining the role played by state housing agencies since the 1970s. Establishing new ground in the field, this volume discusses how the relationship between the federal and state levels has evolved over time. The result, Margaret M. Brassil argues, is that the federal government's broad policy guidelines allow states to better address their own social issues, an improvement for policy and ultimately for the people it serves. --Book Jacket.